2007
DOI: 10.1080/01926230601132030
|View full text |Cite
|
Sign up to set email alerts
|

Asthma/Allergic Airways Disease: Does Postnatal Exposure to Environmental Toxicants Promote Airway Pathobiology?

Abstract: The recent, dramatic increase in the incidence of childhood asthma suggests a role for environmental contaminants in the promotion of interactions between allergens and the respiratory system of young children. To establish whether exposure to an environmental stressor, ozone (O 3 ), and an allergen, house dust mite (HDMA), during early childhood promotes remodeling of the epithelial-mesenchymal trophic unit (EMTU) of the tracheobronchial airway wall by altering postnatal development, infant rhesus monkeys wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 38 publications
2
55
1
Order By: Relevance
“…Additional subchronic and chronic ozone exposure studies (500 ppb) in rhesus monkeys have demonstrated structural changes in the distal and proximal airways (Fanucchi et al, 2006;Carey et al, 2011) and allergy-like patterns of response (increased globlet cells and eosinophils) to allergen and ozone co-challenges (Kajekar et al, 2007;Miller et al, 2009;van Winkle et al, 2010;Plopper et al, 2007). These studies would therefore seem to support the epidemiological observations that reported impaired lung growth (peak flow: Gauderman et al, 2002;FVC and FEV1: Rojas-Martinez et al, 2007) and a worsening of asthma symptoms in children with high ozone exposures (asthma incidence: McConnell et al, 2002;Islam et al, 2009;asthma medication usage: Millstein et al, 2004).…”
Section: Experimental and Panel Studiesmentioning
confidence: 99%
“…Additional subchronic and chronic ozone exposure studies (500 ppb) in rhesus monkeys have demonstrated structural changes in the distal and proximal airways (Fanucchi et al, 2006;Carey et al, 2011) and allergy-like patterns of response (increased globlet cells and eosinophils) to allergen and ozone co-challenges (Kajekar et al, 2007;Miller et al, 2009;van Winkle et al, 2010;Plopper et al, 2007). These studies would therefore seem to support the epidemiological observations that reported impaired lung growth (peak flow: Gauderman et al, 2002;FVC and FEV1: Rojas-Martinez et al, 2007) and a worsening of asthma symptoms in children with high ozone exposures (asthma incidence: McConnell et al, 2002;Islam et al, 2009;asthma medication usage: Millstein et al, 2004).…”
Section: Experimental and Panel Studiesmentioning
confidence: 99%
“…Exposure to allergens during the early years of life leads to a persistent increase in BSM cells by an unknown mechanism, independent of the immune system [1,2]. Therefore, airway remodelling might not be a secondary event, but rather one of the fundamental pathological causes of asthma [3][4][5].…”
mentioning
confidence: 99%
“…The rhesus monkey presents the best model to study lung development, structure and function in the context of the pathogenesis of chronic inflammatory lung diseases [15]. These studies provided first evidence that lung maturation is lastingly altered when mothers were exposed risk factors for asthma or COPD.…”
Section: Epigenetic Programming Of Cell Function On the Level Of Tranmentioning
confidence: 89%
“…Data in cohorts of preterm born people suggest that such a condition during embryogenesis pre-sets the lung to develop asthma or COPD later in life [11,12]. This correlation had been described earlier in rhesus monkeys exposed to ozone or allergens enriched air during pregnancy, which led to permanent rearrangement of airway smooth muscle cells and asthma like symptoms after birth [13][14][15]. These animal studies provided first evidence that exposure to asthma triggers during embryogenesis start a process that alters lung maturation lastingly and which stays active even after the stimulus was removed for long term, suggesting epigenetic events.…”
Section: Introductionmentioning
confidence: 91%